CLINICAL APPLICATION OF HELP-APHERESIS IN FEMALE PATIENT WITH FAMILIAL HYPERCHOLESTEROLEMIA - OLGA L. Barbarash; NATALIA V. Fedorova; VASILIY V. Kashtalap; ROMAN A. Kornelyuk; OLESYA E. Astafurova; DMITRIY L. Shukevich; OLGA V. Gruzdeva (Фундаментальная и клиническая медицина)
Cardiovascular diseases caused by atherosclerosis and its complications represent the leading cause of death in developed countries. The main risk factor of atherosclerosis development is dyslipidemia, in particular familial hypercholesterolemia (FH) characterized by inherited dysregulation of lipid metabolism. Standard medications to control dyslipidemia did not exhibit notable efficacy in patients with FH; instead novel cholesterol-lowering medications (e.g. PCSK9 inhibitors) or extracorporeal treatment such as LDL-apheresis should be applied. Here we present a clinical case of employing HELP-apheresis to treat a female patient with FH. Initially, combined therapy by maximum tolerated dose of statins and ezetimibe demonstrated little if any efficacy. Two sessions of HELP-apheresis showed high efficacy and safety rates. In addition to the main hypolipidemic effect, this method improves blood rheological properties, potentiating anti-atherogenic effects and favoring the prognosis in patients with severe lipid metabolism disorders.